Internal Communication Channels as Operational Thrust in The Nigeria Customs Service - Abdullahi Aliyu Maiwada (Britain International for Academic Research (BIAR) Publisher, 2025)
In an ever-evolving, dynamic, and complex world, the field of public relations has taken on a transformative role in shaping our society. However, the context of internal communication practices within paramilitary agencies, such as the Nigeria Customs Service, diverges from conventional corporate organisational models. This divergence is particularly pronounced given the agency’s multifaceted role in revenue generation, the suppression of smuggling, trade facilitation, and other functions. The study examines the channels of internal communication in the Nigeria Customs Service and the operational thrust of internal communication channels in the Nigeria Customs Service. Situational Theory of Problem Solving is used as a theoretical framework. The study employed a constructivist approach to research design, which informed the choice of in-depth interviews. Purposive sampling was employed to select twelve participants for the study. Data gathered from the interview were presented using thematic analysis, based on the themes that emerged during the interview sessions, using Nvivo, version 14. The findings revealed that while some channels, such as email and in-person meetings, were commonly used for sharing information, there were varying perceptions regarding their effectiveness. Additionally, the study identified challenges in timely disseminating critical operational information, indicating potential gaps in communication effectiveness within the organisation. In evaluating the effectiveness of current internal communication channels, the research found that while some channels were perceived as effective by most respondents, there were also instances where communication was considered ineffective. The study concludes that internal communication is an important concept and integral to internal public relations, and it links to positive organisational and employee outcomes such as employee engagement.